2000
DOI: 10.1007/s004970000047
|View full text |Cite
|
Sign up to set email alerts
|

The translationally repressed pollen-specific ntp303 mRNA is stored in non-polysomal mRNPs during pollen maturation

Abstract: A tobacco pollen tube glycoprotein, p69 is encoded by the pollen-specific gene ntp303 that is transcribed during pollen development and pollen tube growth, but it is abundantly translated only after pollen germination. To investigate the translational repression of ntp303 mRNA during pollen development the compartmentation of ntp303 mRNA was examined and compared against another transcript (ntp52), which is efficiently translated during pollen maturation. Three subcellular fractions were isolated: a post-polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 46 publications
2
50
0
Order By: Relevance
“…The presence of enhanced levels of these factors in anthers and pollen is consistent with previous expression studies showing higher levels of initiation factors in the meristematic regions that contain higher numbers of dividing and expanding cells Rodriguez et al, 1998). Whereas anthers contain actively expanding immature pollen grains, there is good evidence to indicate that early pollen tube growth following germination is strictly dependent upon the efficient translation of mRNAs stored as mRNPs in mature dehydrated pollen (Mascarenhas, 1990;Honys et al, 2000). The translation initiation factors, including NteIF4E, NteIFiso4E, and tobacco T eIF4A are likely to be major constituents of these mRNP complexes.…”
Section: Discussionsupporting
confidence: 88%
“…The presence of enhanced levels of these factors in anthers and pollen is consistent with previous expression studies showing higher levels of initiation factors in the meristematic regions that contain higher numbers of dividing and expanding cells Rodriguez et al, 1998). Whereas anthers contain actively expanding immature pollen grains, there is good evidence to indicate that early pollen tube growth following germination is strictly dependent upon the efficient translation of mRNAs stored as mRNPs in mature dehydrated pollen (Mascarenhas, 1990;Honys et al, 2000). The translation initiation factors, including NteIF4E, NteIFiso4E, and tobacco T eIF4A are likely to be major constituents of these mRNP complexes.…”
Section: Discussionsupporting
confidence: 88%
“…The parameters compared included the ultracentrifugation speed and duration as well as various sucrose concentrations in the cushion. In comparison with the original protocol (60% sucrose cushion; Figure 2A), 33 no changes in the EPP profile and yet a higher yield were obtained after 3 h and 20 min sedimentation though 30% sucrose under 60 000 rpm ( Figure 2C). Alternatively, SEC was employed for the direct isolation of EPP complexes from postmitochondrial supernatant without presedimentation through sucrose cushion.…”
Section: Epps Are Present In Growing Pollenmentioning
confidence: 82%
“…The presence of EPPs in immature and mature pollen was demonstrated previously. 33 During the progamic phase, EPPs were detectable in activated pollen grains after 30 min imbibition in the cultivation medium as well as in growing pollen tubes cultivated in vitro for 4 h and even 24 h (Figure 1). 2-D SDS-PAGE gels were loaded with proteins isolated from an equal amount of mature dry pollen (40 mg).…”
Section: Epps Are Present In Growing Pollenmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it has been demonstrated that RNA-binding proteins are important for post-transcriptional regulation and maturation of transcripts (Palanivelu et al 2000;Coller et al 1998). Furthermore, it has been known that the translation from mRNA was repressed in mature pollen grains (Mascarenhas 1993;Honys et al 2000). Furthermore, Lorkovic et al indicated that AtRBP45s still participated in the undefined steps of pre-mRNA maturation in plants (Lorkovic et al 2000).…”
mentioning
confidence: 99%